1979
DOI: 10.1017/s0043174500043575
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Taxonomic Study of Portulaca oleracea

Abstract: A phenetic classification of 44 ecotypes of common purslane (Portulaca oleracea L.) produced 4 major groups: cool temperate; warm temperate to wet dry subtropic; humid subtropic to tropic; and cultivated. These groups were based on 36 plant characteristics; the ecotypes were collected from 18 countries and are representative of climates inhabited by common purslane. The cultivated group is comprised of robust forms which are raised for culinary purposes. For weed forms, plants of the cool temperate group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A comprehensive phylogeny including as many accessions of P. oleracea as possible will be needed to solve the species paraphyletic scenario, but its cosmopolitan distribution may prove to be a challenge to this goal. In the present study, we selected genotypes sampled from independent populations and identified as different subspecies, and the clustering methods applied here confirmed previously described trends 38 , where weedy (small, prostrate and branched) phenotypes were clustered separately from more robust and erect phenotypes, e.g. commercial cultivars.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…A comprehensive phylogeny including as many accessions of P. oleracea as possible will be needed to solve the species paraphyletic scenario, but its cosmopolitan distribution may prove to be a challenge to this goal. In the present study, we selected genotypes sampled from independent populations and identified as different subspecies, and the clustering methods applied here confirmed previously described trends 38 , where weedy (small, prostrate and branched) phenotypes were clustered separately from more robust and erect phenotypes, e.g. commercial cultivars.…”
Section: Discussionmentioning
confidence: 55%
“…It also presents a cosmopolitan distribution, occurring in most tropical and subtropical regions 36 . Variations in chromosome number 37 , vegetative and reproductive morphology 38 42 are already described between accessions of this species. Because of such high phenotypical plasticity, P. oleracea is sometimes referred to as a polymorphic species 33 , 37 , or even subdivided into different subspecies 43 , 44 or microspecies 45 – 47 that form a taxonomic aggregate or complex.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Gorske, Rhodes & Hoppen () demonstrated that the cultivated forms can be separated by, among other morphological characters, seed size from the wild representatives of the P. oleracea complex. The taxonomic value of seed characters, however, for the discrimination of the wild representatives is uncertain.…”
Section: Discussionmentioning
confidence: 99%